Monetary Policy Transmission to Financial System Stability in Aceh and Indonesia: ARDLECM Approach (Monthly Data January 2020June 2025) - Shifa, Mutiara (Riwayat: Educational Journal of History and Humanities, 2025)
Financial system stability is a crucial element in maintaining sustainable economic growth and the effectiveness of monetary policy, particularly in developing countries with complex economic dynamics. This study aims to analyze the transmission of monetary policy to financial system stability in Aceh and Indonesia using a quantitative approach based on monthly time series data from January 2020 to June 2025. The research variables include policy interest rates, inflation, exchange rates, and bank credit as indicators of monetary transmission, and the financial system stability index as the dependent variable. The analysis method uses the Autoregressive Distributed Lag (ARDL) to identify long-term relationships and the Error Correction Model (ECM) to analyze short-term adjustment dynamics. The analysis stages include descriptive statistics, stationarity tests, bounds testing, ARDL estimation, ECM estimation, and model diagnostic tests that include autocorrelation, heteroscedasticity, normality, and parameter stability. The results show that interest rates and inflation have a significant negative effect on long-term financial system stability, while bank credit has a positive effect on stability through an increase in the intermediation function. The exchange rate has a significant influence through the external risk channel that influences financial sector volatility. A significant error correction coefficient indicates the existence of an adjustment mechanism toward long-run equilibrium. This finding confirms that monetary policy plays a crucial role in maintaining regional and national financial system stability through various transmission channels